Immunohistochemical Characterisation of GLUT1, MMP3 and NRF2 in Osteosarcoma - Rutland, Catrin S.; Cockcroft, James M.; Lothion-Roy, Jennifer; Harris, Anna E.; Jeyapalan, Jennie N.; Simpson, Siobhan; Alibhai, Aziza; Bailey, Clara; Ballard-Reisch, Alyssa C.; Rizvanov, Albert A.; Dunning, Mark D.; de Brot, Simone; et al. (Frontiers in Veterinary Science, 2021)
Osteosarcoma (OSA) is an aggressive bone malignancy. Unlike many other malignancies, OSA outcomes have not improved in recent decades. One challenge to the development of better diagnostic and therapeutic methods for OSA has been the lack of well characterized experimental model systems. Spontaneous OSA in dogs provides a good model for the disease seen in people and also remains an important veterinary clinical challenge. We recently used RNA sequencing and qRT-PCR to provide a detailed molecular characterization of OSA relative to non-malignant bone in dogs. We identified differential mRNA expression of the solute carrier family 2 member 1 (SLC2A1/GLUT1), matrix metallopeptidase 3 (MMP3) and nuclear factor erythroid 2–related factor 2 (NFE2L2/NRF2) genes in canine OSA tissue in comparison to paired non-tumor tissue. Our present work characterizes protein expression of GLUT1, MMP3 and NRF2 using immunohistochemistry. As these proteins affect key processes such as Wnt activation, heme biosynthesis, glucose transport, understanding their expression and the enriched pathways and gene ontologies enables us to further understand the potential molecular pathways and mechanisms involved in OSA. This study further supports spontaneous OSA in dogs as a model system to inform the development of new methods to diagnose and treat OSA in both dogs and people.